0454 Response to Lemborexant in Older Subjects with Insomnia Disorder and Comorbid Pain at Baseline. (25th May 2022) - Kaplan, Alan; Cheng, Jocelyn; Suzuki, Masahiro; Kumar, Dinesh; Malhotra, Manoj; Moline, Margaret; Pappadopulos, Elizabeth
Abstract: Introduction: The reciprocal relationship between pain and poor sleep has been well established. Pain interferes with sleep, and insomnia increases pain sensitivity, thus reducing quality of life. Therefore, it is of clinical importance to evaluate whether a sleep-promoting drug such as the dual orexin receptor antagonist, lemborexant (LEM; approved in multiple countries to treat adults with insomnia) can improve sleep in older patients, in whom both sleep and ongoing pain are prevalent. Methods: Study 304 (NCT02783729), was a 1-month, double-blind, PBO- and active-controlled study in subjects age ≥55y with insomnia (full analysis set [FAS]=1006). Those who also endorsed some/severe pain at baseline on the pain/discomfort dimension of the EuroQual-5 Dimension-3 Level scale (EQ-5D-3L; no problems/some problems/extreme problems) at baseline were eligible for these post-hoc analyses. Medical history of pain conditions and/or ongoing therapy were not required for eligibility and were not evaluated. Subjects were randomized to bedtime doses of placebo, LEM 5mg (LEM5), 10mg (LEM10) or zolpidem tartrate extended release (not reported here). Changes from baseline (CFB) in objective sleep parameters assessed by polysomnography (latency to persistent sleep [LPS]; wake after sleep onset [WASO]) were analyzed by mixed-effect repeated measures analyses adjusted for relevant factors. Results: Approximately 18% of the FAS reported some or extreme pain at baseline (PBO=55; LEM5=78; LEM10=50). For LPS, baseline median values (minutes) were 31.0, 29.4 and 42.1 for PBO, LEM5 and LEM10, respectively. Median CFB for LPS were larger and statistically significantly different for both LEM doses compared with PBO at the beginning of treatment (mean of Nights 1/2: +2.5; -8.4, -15.8; P<0.005); and were (mean of Nights 29/30: -7.1, -9.9, -9.0) at the end of treatment LEM5 (P=0.031), LEM10 (P=0.054). For WASO, baseline median values (minutes) were 101.0, 103.6 and 111.1 for PBO, LEM5 and LEM10, respectively. Median CFB for WASO were larger and statistically significantly different (P<0.001) for both LEM doses compared with PBO at the beginning (Nights 1/2; -1.5; -41.5, -64.4) and end of treatment (Nights 29/30; -1.1, -37.9, -52.5). Conclusion: These data suggest that lemborexant can effectively treat insomnia in older adults with concomitant painful conditions. Support (If Any): Eisai Inc.